A Syrian Refugee in Iraq Diagnosed as a Case of IL12RB1 Deficiency in Japan Using Dried Blood Spots - Al-Kzayer, Lika'a Fasih Y.; Yassin, Ahmed K.; Salih, Khalid Hama; Shigemura, Tomonari; Sano, Kenji; Al-Simaani, Ruwaid Behnam Y.; Tanaka, Miyuki; Nakazawa, Yozo; Okuno, Yusuke (Frontiers in Immunology, 2019)
Mendelian susceptibility to mycobacterial diseases (MSMD) is a rare condition of primary immunodeficiency disorder. Interleukin-12 receptor β1 (IL12RB1) deficiency, is the most common genetic etiology of MSMD, which is characterized by the selective predisposition to clinical disease caused by weakly-virulent mycobacteria, such as Bacillus Calmette-Guérin (BCG) vaccines, and environmental non-tuberculous mycobacteria (NTM). To the best of our knowledge, this is the first case of IL12RB1 deficiency to be reported from Iraq. Our case is an 8-year-old Syrian girl, for first-cousin parents, with a refugee-status in the North of Iraq. She had a history of disseminated BCG infection two months after receiving BCG vaccine, in addition to repeated episodes of mild or severe illnesses, such as maculopapular skin rash, lymphadenopathy, gastroenteritis, meningitis and clinically diagnosed tuberculosis (TB) based on local TB-prevalence setting. Because of limited medical facilities in the war-torn countries; in Syria and Iraq, no diagnosis could be reached. We used Flinders Technology Associates (FTA) cards to transfer her bone marrow aspirate to Japan. A homozygous IL12RB1 mutation was detected by whole exome sequencing in Japan, using genomic-DNA extracted from dried blood spots on FTA filter paper. In conclusion, diagnosis of MSMD due to IL12RB1 deficiency was possible by transferring the FTA sample of the patient for genetic evaluation in Japan. Our report recalls the need of pediatricians in countries with TB-prevalence and high parental consanguinity, to consider IL12RB1 deficiency in the differential diagnosis of a child with clinical evidence of TB, especially with the history of disseminated BCG disease.